Pathogenesis of an attenuated and a virulent strain of group A human rotavirus in neonatal gnotobiotic pigs - Lucy Ward; B I Rosen; Lijuan Yuan; Linda J. Saif (1996)
Gnotobiotic (Gn) pigs were orally inoculated with Wa strain (G1P1A[P8]) human rotavirus (Wa HRV) serially passaged in Gn pigs (virulent) or cell culture (attenuated) to determine the median virus infectious dose (ID50) and to assess the site of infection and type and progression of morphological lesions and clinical responses induced by these two strains in Gn pigs. The ID50 of virulent Wa HRV was ⩽ 1 f.f.u. whereas the infectivity of attenuated Wa HRV had to be determined by seroconversion and was ∼ 1.3 × 106 f.f.u. Diarrhoea developed at 13 h post-inoculation (p.i.) in pigs inoculated with ∼ 105 f.f.u. of virulent Wa HRV and correlated with the presence of viral antigen within villous epithelial cells; villous atrophy developed later at 24 h p.i. and correlated with peak faecal viral titres; recovery from disease correlated with the return of morphologically normal villi. Virus, diarrhoea and villous atrophy were not detected in pigs inoculated with ∼ 2 × 108 f.f.u. attenuated Wa HRV although HRV-specific serum antibodies were present by 7 days p.i. These findings demonstrate that virulent Wa HRV infection in Gn pigs occurs primarily within intestinal villous epithelial cells with villous atrophy developing as a sequela to infection. However, factors other than villous atrophy appear to contribute to the early stages of HRV-associated disease expression in Gn pigs. The ability of the attenuated virus to elicit virus-neutralizing serum antibodies without disease or pathology indicates promise in the use of such strains for oral immunization.